Is the press depoliticizing (neoliberal) laws that reconfigure citizenship and migration? The case of investment visas in Portugal - Santos, T. R.; Castro, P.; Guerra, R. (ISPP 2019 Empowering Citizens in Illiberal Times: The Political Psychology of Oppression and Resistance, 2019)
Neoliberalism calls upon political psychology to explore how neoliberal legal innovations are reconfiguring citizenship. Investment Visas, regulating foreign residency and migration, prioritize economic capital from space bound involvement in the host country - it thus reconfigures citizenship representations and differentiates sub-groups of foreign residents. These transformations, however, can be presented as depoliticized in the public sphere, i.e., as economically ‘inevitable’. This in turn helps close down possible (political) contestation and citizenship involvement. This presentation focuses then on how the Portuguese Press presented the Investment Visa law to the public sphere in connection with a particular foreign community: the Chinese in Portugal – a rapidly growing group using both traditional migration laws and Investment Visas. We specifically aim at exploring the representation of the Chinese in the press, to uncover (1) whether the Chinese are presented as a unified community, or if the Investment Visa beneficiaries come out as a different sub-group, and (2) whether the presentation of the Chinese Investment Visas is a depoliticized one, highlighting economic benefits only, and excluding other citizenship-related values, in the mainstream press (quality and tabloid). The analysis is two-fold. First, 525 articles about ‘Chinese’ and ‘Portugal’ from two newspapers (a quality one, Público n= 287 and a tabloid one, Correio da Manhã n=238) were submitted to thematic analysis by IraMuTeQ software. Second, we focus only on articles mentioning Investment Visas (n=164; Público n= 83 and Correio da Manhã n=81), undertaking a content analysis to explore the existence of the characteristics of depoliticized discourse. Results show that Chinese residents by Investment Visas are disconnected from other residents. Furthermore, the ways in which Investment Visas are presented in the press shows signs of depoliticization – by showing one (uncontested) perspective on the issue. Conflicting values and dimensions, such as a de-territorialized and investment-based notion of citizenship, are almost absent, and left un-problematized. Implications for the psychology of (neoliberal) citizenship and migration are discussed.